EXPLORING FACTORS INFLUENCING STUDENTâS MOTIVATION IN ENGLISH LEARNING - ., Hersulastuti (MAGISTRA, 2012)
Motivation plays a vital role in language learning. In many cases, students often face difficulties to obtain success in learning due to the motivation they have. This paper aims at exploring some factors influencing studentsâ motivation in English learning. The data are derived from the informal interview conducted to ten students of the sixth semester of English Education Program of Widya Dharma University, Klaten in 2011. Other supporting data are used to strengthen the results taken from the studentsâ comments at the end of the semester, obtaining three factors influencing studentsâ motivation, namely worthwhile goals and clear objectives, self-confidence, and a variety of activities and interaction. Key Words: motivation, language learning, worthwhile goals, self-confident, interaction